2005
DOI: 10.1161/01.hyp.0000152079.04553.2c
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure and 10-Year Risk of Cardiovascular and Noncardiovascular Mortality

Abstract: Abstract-The objective of this study was to elucidate the long-term prognostic significance of ambulatory blood pressure.Ambulatory and casual blood pressure values were obtained from 1332 subjects (872 women and 460 men) aged Ն40 years from the general population of a rural Japanese community. Survival was then followed for 14 370 patient years and analyzed by a Cox hazard model adjusted for possible confounding factors. There were 72 cardiovascular deaths during the 10.8-year follow-up. The relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
226
2
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(246 citation statements)
references
References 32 publications
9
226
2
9
Order By: Relevance
“…15 Given the potential inaccuracies in measurement technique and artificial increases in BP produced by 'white-coat' effects, 2 office or clinic BP measurement could be inferior to ABPM in predicting hypertension-induced organ damage or clinical outcome. [3][4][5][6] In the current study, office BP parameters including SBP, DBP and even PP failed to predict any clinical outcome. On the other hand, ambulatory BP parameters such as 24 h, daytime and nighttime PP predicted not only CVD and mortality but also non-CV and all-cause mortality, suggesting their broad prognostic impacts in hypertensive patients.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…15 Given the potential inaccuracies in measurement technique and artificial increases in BP produced by 'white-coat' effects, 2 office or clinic BP measurement could be inferior to ABPM in predicting hypertension-induced organ damage or clinical outcome. [3][4][5][6] In the current study, office BP parameters including SBP, DBP and even PP failed to predict any clinical outcome. On the other hand, ambulatory BP parameters such as 24 h, daytime and nighttime PP predicted not only CVD and mortality but also non-CV and all-cause mortality, suggesting their broad prognostic impacts in hypertensive patients.…”
Section: Discussioncontrasting
confidence: 53%
“…2 Many studies have confirmed superiority of 24-h ambulatory BP monitoring (ABPM) over office or clinic BP measurement in predicting hypertension-induced organ damage or clinical outcome. [3][4][5][6] To what extent ABPM provides an independent predictive value beyond office BP is of clinical importance, as ABPM is potentially more burdensome and associated with higher costs than office or clinic BP measurements. Previous study mainly focused on ambulatory systolic BP (SBP) 3,4,6,7 or diastolic BP (DBP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ABP is a better predictor of target organ damage, cardiovascular morbidity and mortality than office BP, 68 it is of great interest to know whether 24-h BP will be a better phenotype than office BP to find genes for EH. To date, four twin studies 2528 and three family studies 2931 have reported heritability estimates for 24-h ABP recording.…”
Section: Discussionmentioning
confidence: 99%
“…5 The added value of ABP measurements has indeed been illustrated by studies showing that ABP is a better predictor of target organ damage and cardiovascular morbidity and mortality than BP measured in the clinic. 68 …”
Section: Introductionmentioning
confidence: 99%